The prognostic utility of baseline alpha‐fetoprotein for hepatocellular carcinoma patients. Issue 7 (25th July 2017) - Silva, Jack P.; Gorman, Richard A.; Berger, Nicholas G.; Tsai, Susan; Christians, Kathleen K.; Clarke, Callisia N.; Mogal, Harveshp; Gamblin, T. Clark
Abstract : Introduction: Alpha‐fetoprotein (AFP) has a valuable role in postoperative surveillance for hepatocellular carcinoma (HCC) recurrence. The utility of pretreatment or baseline AFP remains controversial. The present study hypothesized that elevated baseline AFP levels are associated with worse overall survival in HCC patients. Methods: Adult HCC patients were identified using the National Cancer Database (2004‐2013). Patients were stratified according to baseline AFP measurements into the following groups: Negative (<20), Borderline (20‐199), Elevated (200‐1999), and Highly Elevated (>2000). The primary outcome was overall survival (OS), which was analyzed by log‐rank test and graphed using Kaplan‐Meier method. Multivariate regression modeling was used to determine hazard ratios (HR) for OS. Results: Of 41 107 patients identified, 15 809 (33.6%) were Negative. Median overall survival was highest in the Negative group, followed by Borderline, Elevated, and Highly Elevated (28.7 vs 18.9 vs 8.8 vs 3.2 months; P  < 0.001). On multivariate analysis, overall survival hazard ratios for the Borderline, Elevated, and Highly Elevated groups were 1.18 ( P  = 0.267), 1.94 ( P  < 0.001), and 1.77 ( P  = 0.007), respectively (reference Negative). Conclusion: Baseline AFP independently predicted overall survival in HCC patients regardless of treatment plan. A baseline AFP value is a simple and effective method to assist in expected survival for HCC patients.